Implementation Failure of Fund Allocation and Management Policy for Project Preparation and Readiness: An Analytical Appraisal (Bangladesh Journal of Public Administration, 2019)
Economic Relations Division (ERD) formulated “Fund Allocation and Management policy for ProjectPreparation and Readiness” on 6 March 2017 to provide financial support for feasibility study andland acquisition at the project preparation stage of various Ministries/Divisions of the Government ofBangladesh. Despite such efforts, ERD did not get any response from relevant Ministries/Divisions toimplement the policy. The paper critically examines the causes behind the implementation failure ofthe policy. The study found that officials of the project implementing Ministries/Divisions were notwell informed about the policy in particular. Moreover, the Ministries/Divisions, which have severalinitial roles to play in order to bring implementation process on board, have hardly done anything toprove that the existing bureaucratic set up is reluctant to take proactive initiatives to implement newpolicies unless they are somehow forced by the external environment. Besides, there exists a similarkind of fund, allocated in favour of the Programming Divisions of the Ministry of Planning, whichallow the project implementing Ministries/Divisions to get financial allocation for a feasibility studyat the project preparation stage. This similar kind of fund may decrease the importance of the ERDformulated fund for project readiness. Similarly, absence of allocation in the right place is also one ofthe root causes for implementation failure. Considering the findings, among others, recommendationsinclude holding of workshops for further dissemination of the policy documents and the scope andresponsibilities of each Ministry/Division.